The atomized body : the cultural life of stem cells, genes and neurons - Liljefors, Max, 1963-; Lundin, Susanne; Innodata Copy (Nordic Academic Press, 2012)
Referring to the focus of the biosciences on molecular ""particles"" of the human biology-such as stem cells, genes, and neurons-this account examines the relationships between culture, society, and bioscientific research. Showing that the atomized body is indeed socially and culturally embedded, in plural and complex ways, it argues that biomedicine and biotechnology do not only intersect with the human body, but also reshape our perceptions of selfhood and life. From a multidisciplinary perspective, this volume explores the biosciences and the atomized body in their social, cultural, and phi